(untitled) (Journal of Pharmaceutical Negative Results, 2023)
As firms seek ways to manage customer relationships over the long term, understanding the dynamics of the service provider-customer relationship becomes a key priority. The purpose of investigation is to examine the relationship(s) among service quality, customer satisfaction and customer commitment in the community pharmacy. The study was conducted in five different community pharmacies, all located in the city of Vijayawada, Andhra Pradesh. The study population consisted of the customers of those five pharmacies. The researcher chose a convenience sample of the customers, who visited those pharmacies during the period of the study, which consists of 250 respondents. The Statistical Package for Social Sciences (SPSS) program was used to examine the hypotheses.